Flexible Conducting Polymer Electrodes for Selective Stimulation of Small Sensory Fibers in Humans. Issue 1 (15th September 2022) - Velasco‐Bosom, Santiago; Gurke, Johannes; Han, Sanggil; Lee, Michael C.; Malliaras, George G.
Abstract: Small‐fiber neuropathy (SFN), a pathology caused by severe loss of free‐endings of unmyelinated sensory nerves, is difficult to diagnose and monitor. The use of cutaneous electrical stimulation as a diagnostic tool is hampered by the fact that the injected current penetrates deep into the skin and stimulates many other receptors. Interdigitated electrodes are recently proposed to control the depth of current penetration and selectively address small‐fibers. Here, flexible and adhesive interdigitated electrodes made of Au coated with poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) are developed, that conform comfortably and reliably to human skin. It is shown that the PEDOT:PSS coating improves safety by significantly reducing the voltage required to inject current. The selectivity of the device is assessed by showing that it elicits a significantly slower reaction time than commercial cutaneous electrophysiology electrodes, as it exclusively activates unmyelinated fibers. The device is further evaluated on volunteers that undergo local capsaicin treatment to induce temporary loss of the nerve endings of small‐fibers. Pre‐ and post‐treatment electrical stimulation of the affected area with the device reveals impaired sensory detection that is not observed with commercial cutaneous electrophysiology electrodes. These results represent a significant step towards the use of electrical stimulation as a diagnostic and monitoring tool for SFN. Abstract : The development of cutaneous electrodes for the selective stimulation of small sensory fibers in humans is reported. The electrodes are assessed by measurements of reaction time and stimulation current threshold. A poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate coating is shown to make the electrodes safer and more reliable. The results support the development of a non‐invasive diagnostic for small‐fiber neuropathy.